(untitled) (Somma: Revista Científica do Instituto Federal do Piauí, 2024)
The spiral nematode, Helicotylenchus multicinctus, is present in production areas of various agricultural crops around the world and in Brazil, standing out as the main nematode causing damage to banana cultivation. Given the importance of this pathogen, this work aimed to determine the sequence of the ITS and 28S rDNA regions of H. multicinctus and explore the phylogenetic position of H. multicinctus isolated from Brazil. After collection, nematodes were extracted from the samples and morphological and molecular identification was carried out and, through Bayesian analysis of 28S rDNA, the phylogenetic position of H. multicinctus was inferred. The morphological and molecular data of this study identified H. multicinctus associated with banana farming in Limoeiro do Norte and H. multicinctus from Brazil grouped with the other H. multicinctus isolates in the world presenting high Bootstrap values within Clade XI.